Questions and Answers on Prothrombin Time Standardisation in Oral Anticoagulant Control - Loeliger, E A; Poller, L; Samama, M; Thomson, J M; Van den Besselaar, A M H P; Vermylen, J; Verstraete, M (Thrombosis and Haemostasis, 1985)
One of the reasons why oral anticoagulants fell into disrepute is the absence of internationally accepted standardised procedures for controlling the level of anticoagulatiori. This deplorable situation resulted in over- and under-coagulation and uncertainty in the therapeutic range. International conformity can now be obtained by using an International Normalised Ratio (INR) which is derived from the individual result obtained in a given plasma sample and the International Sensitivity Index (ISI) of the tissue thromboplastin reagent used. Any thromboplastin reagent can be calibrated against an international primary or secondary W.H.O. reference preparation, so as to obtain its International Sensitivity Index. The new system of reporting the level of anticoagulation was designed and can only safely be applied in patients taking oral anticoagulants.
Keywords: Prothrombin time; Oral anticoagulants; International normalised ratio; International sensitivity index; Standardisation